LIBS plasma in atmospheric pressure argon, nitrogen and helium: Spatio-temporal distribution of plume emission and Hα linewidth - Jogi, Indrek; Ristkok, Jasper; Butikova, Jelena; Raud, Jüri; Paris, Peeter (Elsevier, 2023)
Laser Induced Breakdown Spectroscopy (LIBS) method is considered for assessing the retention of hydrogen isotopes in the ITER plasma-facing components during the maintenance breaks when the reactor is filled with near atmospheric pressure nitrogen or inert gas. At these conditions, the broadening of the spectral lines of hydrogen isotopes and the reduction of line intensities complicates the distinguishing of hydrogen isotopes. The aim of the present study was to investigate the effect of atmospheric pressure nitrogen, argon and helium ambient gas on the spatio-temporal distribution of the LIBS plasma plume emission and linewidths of Hα line, representing the hydrogen isotopes. Nd:YAG laser with 8 ns pulse width was used to ablate the molybdenum (Mo) target with hydrogen impurity. The development of the formed plasma plume was investigated by time and space-resolved emission spectra in the 20 nm range around the 656.28 nm Hα line. For all gases used in the experiments, the intensity and linewidth of Hα line decreased with the delay time between the laser pulse and the spectral registration. At the same linewidth values, the highest intensities were obtained in the helium atmosphere while the lowest intensity was obtained in nitrogen. According to spatially resolved spectral measurements, the Hα line was most intense near the Mo target while the Mo lines peaked farther away. In the case of the helium atmosphere, the plasma plume emission was observed at a longer distance from the target and it decayed faster than in argon and nitrogen atmospheres. According to these results, helium is the most beneficial ambient gas for hydrogen isotope detection by atmospheric pressure LIBS. The use of argon ambient gas may be required when LIBS is used for the simultaneous determination of fuel and He retention in the wall material. --//-- This is an open access article Indrek Jõgi, Jasper Ristkok, Jelena Butikova, Jüri Raud, Peeter Paris, LIBS plasma in atmospheric pressure argon, nitrogen and helium: Spatio-temporal distribution of plume emission and Hα linewidth, Nuclear Materials and Energy, Volume 37, 2023, 101543, ISSN 2352-1791, https://doi.org/10.1016/j.nme.2023.101543 published under the CC BY-NC-ND licence.
This work has been carried out within the framework of the EUROfusion Consortium, funded by the European Union via the Euratom Research and Training Programme (Grant Agreement No 101052200—EUROfusion). Views and opinions expressed are however those of the author(s) only and do not necessarily reflect those of the European Union or the European Commission. Neither the European Union nor the European Commission can be held responsible for them. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Laser Induced Breakdown Spectroscopy; Fuel retention; Hydrogen isotope determination; Laser induced plasma plume